The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pharmaceutics12090843
|View full text |Cite
|
Sign up to set email alerts
|

A Colon-Targeted Prodrug, 4-Phenylbutyric Acid-Glutamic Acid Conjugate, Ameliorates 2,4-Dinitrobenzenesulfonic Acid-Induced Colitis in Rats

Abstract: An elevated level of endoplasmic reticulum (ER) stress is considered an aggravating factor for inflammatory bowel disease (IBD). To develop an ER-stress attenuator that is effective against colitis, 4-phenylbutyric acid (4-PBA), a chemical chaperone that alleviates ER stress, was conjugated with acidic amino acids to yield 4-PBA-glutamic acid (PBA-GA) and 4-PBA-aspartic acid (PBA-AA) conjugates. The PBA derivatives were converted to 4-PBA in the cecal contents, and the conversion was greater with PBA-GA than t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…This is not surprising since ER stress is emerging as a key signaling pathway involved in IBD pathogenesis and tissue dysfunction, driving the onset of inflammation [16,38,39]. It is also important to note that these results support the reliability of our model since a DNBS-mediated ER stress induction has also been described in an animal model of IBD [40]. Interestingly, the upregulation of these markers seems to be dose-dependent, potentially indicating increased tissue damage related to drug concentration, as also indicated by the dose-dependent upregulation of the stress protein TG2 [12].…”
Section: Discussionsupporting
confidence: 77%
“…This is not surprising since ER stress is emerging as a key signaling pathway involved in IBD pathogenesis and tissue dysfunction, driving the onset of inflammation [16,38,39]. It is also important to note that these results support the reliability of our model since a DNBS-mediated ER stress induction has also been described in an animal model of IBD [40]. Interestingly, the upregulation of these markers seems to be dose-dependent, potentially indicating increased tissue damage related to drug concentration, as also indicated by the dose-dependent upregulation of the stress protein TG2 [12].…”
Section: Discussionsupporting
confidence: 77%
“…It is worthy of noting that Jonathan H. Lin et al demonstrated that human embryonic kidney (HEK) 293 cells pretreated with TM or thapsigargin (TG) (the SERCA ATPase sarco-endoplasmic reticulum Ca 2+ -ATPases inhibitor) exhibited ER stress with an evaluation of Xbp-1s mRNA level detected by reverse transcription-polymerase chain reaction (RT-PCR) and its protein levels tested by western bolting, which indicated IRE1 activation. To further assess the effect of IRE, through selectively upregulating IRE1 activity by treating HEK293 cells with adenosine triphosphate (ATP) analog 4-amino-1-tert-butyl-3-(1′-naphthylmethyl) pyrazolo ( Kim et al, 2020 ) pyrimidine (1NM-PP1), results indicated that the number of surviving cells is much higher ( Lin et al, 2007 ). Furthermore, normal human colon epithelial cell line (NCM-460) cell viability was significantly reduced upon IRE-1 RNA interference.…”
Section: Er Stress and Its Molecular Mechanism Of Signaling Pathwaymentioning
confidence: 99%
“…Colon-targeted prodrugs of 4-PBA were designed and synthesized, and their colon-targeting property was evaluated. Furthermore, the drug’s effectiveness was shown by regulating ER stress in a model of colitis in rats ( Kim et al, 2020 ).…”
Section: Treatment Of Intestinal Diseases Targeting Er Stressmentioning
confidence: 99%
“…Distribution coefficient of AS-DpS-AS was determined using water/1-octanol system as previously described [ 26 ]. The chemical stability of AS-DpS-AS was evaluated in pH 1.2 HCl-NaCl buffer and pH 6.8 isotonic phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%